Normative Experience in Internet Politics - Françoise Massit-Folléa, Cécile Méadel, Laurence Monnoyer-Smith (dir.) (Presses des Mines, 2012)
The ways in which the Internet is managed and controlled -often labeled as Internet Governance- are usually considered as standing on four main pillars: Technology, Market Laws, State Regulation and Uses. Nevertheless, its specific features, the consequences of the plurality of norms it involves and of the decision-making processes it entails are rarely addressed in a comprehensive analysis. This book explores the Internet's functioning both as a practical-intellectual experience and a politi...